From Ivacaftor to Triple Combination: A Systematic Review of Efficacy and Safety of CFTR Modulators in People with Cystic Fibrosis - Gramegna, Andrea (Int J Mol Sci, 2020)
Over the last years CFTR (cystic fibrosis transmembrane conductance regulator) modulators have shown the ability to improve relevant clinical outcomes in patients with cystic fibrosis (CF). This review aims at a systematic research of the current evidence on efficacy and tolerability of CFTR modulators for different genetic subsets of patients with CF. Two investigators independently performed the search on PubMed and included phase 2 and 3 clinical trials published in the study period 1 January 2005–31 January 2020. A final pool of 23 papers was included in the systematic review for a total of 4219 patients. For each paper data of interest were extracted and reported in table. In terms of lung function, patients who had the most beneficial effects from CFTR modulation were those patients with one gating mutation receiving IVA (ivacaftor) and patients with p.Phe508del mutation, both homozygous and heterozygous, receiving ELX/TEZ/IVA (elexacaftor/tezacaftor/ivacaftor) had the most relevant beneficial effects in term of lung function, pulmonary exacerbation decrease, and symptom improvement. CFTR modulators showed an overall favorable safety profile. Next steps should aim to systematize our comprehension of scientific data of efficacy and safety coming from real life observational studies.